DRIVING AND AGING: AGE-RELATED IMPAIRMENT IN SPEED TASKS OF VISUOMOTOR ANTICIPATION AND COORDINATION - Romero Medina, Agustín; García Sevilla, Julia; Martínez Sánchez, Francisco; Morales, Amalia; Sánchez Meca, Julio (Anales de Psicología / Annals of Psychology)
The relation between age and two psychomotor skills (speed of anticipation and visuomotor bimanual coordination) are analysed. The DRIVER TEST battery is utilized in 551 male adults in five age groups: (1) 61 subjects 15 to 17 age olders, (2) 241 subjects 18 to 37 age olders, (3) 131 subjects 38 to 57 age olders, (4) 84 subjects 58 to 71 age olders, and (5) 34 subjects 72 to 84 age olders. No differences between age groups are found in speed of anticipation task (Experiment I), against initial hypothesis. In visuomotor coordination task (Experiment II), 4 and 5 groups are a poor performance that young males, but also the olders are a punctuation more sparse that youngers.